The Ecotourism Appropriacy of Busung Village - Primantoro Nur Vitrianto; Tyas Rosani (International Journal Labs, 2023)
Busung Village is located in Bintan Regency and has a viral attraction: A Desert and Telaga Biru. This tourism destination managed by the local community called Kelompok Sadar Wisata, now become an interesting natural attraction. Referring to the Bintan Government Regulation Number 1 of 2020 about the Regency Spatial Planning Policy, Busung Village is the part of Industrial Area. Meaning that the Desert and Telaga Biru are located inside the industrial area. To develop a tourism destination is not only to develop the 4A, Attraction, Accessibility, Amenity, and Ancillary Services only, but it needed a site suitability evaluation. This research aims to evaluate of site suitability of Busung Village based on ecotourism criteria. The other purpose is to provide development guidance for Busung village in the future. This research is using the mixed method, the quantitative is used to evaluate the site's suitability for ecotourism. To explain the ecotourism suitability index using the descriptive method. Data were analyzed by spatial analysis and software Geographic Information System (GIS). The result showed that the ecotourism suitability index for sample I is 71,34% and for sample II is 70,12%. All samples in the S2 category mean that areas are suitable for ecotourism. Based on the spatial map, the development guidance for the Desert and Blue Lake area is 18,49 hectares for ecotourism activity.